The effect of a four-week mesocycle with small side games on the agility and printing ability of professional soccer players during in-season - Komsis, S.; Komsis, T.; Komsis, G.; Papadopoulou, Z.; Thomas, M.; Gissis, I.; Vrabas, I. S. (Journal of Physical Education and Sport, 2023)
Despite the extensive use of SSGs training in soccer, our knowledge about their effectiveness as a training tool for developing physical, technical and tactical skills in soccer players is not complete (Hill-Haas et al., 2011). The aim of the present study is to examine the effects of a 4-week SSGs training intervention on the agility and sprinting ability of professional soccer players in season. Twenty-four male professional soccer players (3 Central Defender, 4 Full Backs,4 Central Midfielders, 4 Attack Midfielders, 6 Wingers, 3 Strikers) with age (26±3,45y), height (1,81± 3,78m), body weight (75,23±5,62 kg), BMI (24,17 ±1,59kg/m2) of second professional Greek league participated in this study. They were randomly assigned to small side games training group (SSG, n=12) or a control group (CG, n=12). This study was conducted in season, when participants attended soccer training sessions five times per week and played competitive matches at least once a week. In order to examine the changes in agility and sprinting ability after the 4-week meso-cycle periodized small side games training, all players were tested two times, pre and post of the intervention. Body mass was measured the same days of testing but in the morning before breakfast. All the test sessions were carried out on a grass soccer field after a typical 15min soccer warm up. The order of the tests was 30m linear sprint and illinoise agility test. Statistical analysis was conducted using SPSS 18.0 for Windows and the significance level was set at P=0.05. Data were tested with two-way analysis (2x2 ANOVA) with repeated measure (groups x measurement). In variables that were significant interaction we continue with paired t test. Results showed that there was statistically significant interaction in Agility with p=0,000, t= 4,458 and there was no statistically significant interaction in 30m Sprint with p=0,770, t= 0,298, in Bodyweight with p=0,245, t= 0,809 and in BMI with p=0,994, t= 0,809.